Pattern and distribution of cardiac diseases in children attending the Karnali Academy of Health Sciences, Jumla - Thani, Kamal Prasad; Shrestha, Sandeep; Gautam, Uttara; Keshari, Munna (Janaki Medical College Journal of Medical Science, 2026)
Background & Objectives: Childhood cardiac diseases remain a significant health burden in Nepal, particularly in remote regions where access to specialized care is limited. This study aimed to determine the pattern and distribution of cardiac diseases among children attending Karnali Academy of Health Sciences (KAHS), Jumla.Materials and Methods: A retrospective hospital-based study was conducted reviewing medical records of pediatric patients aged 0-18 years diagnosed with cardiac diseases between January 2023 and December 2024. Data were extracted from outpatient, inpatient, and echocardiography registers using a structured checklist. Descriptive statistics and chi-square tests were performed using SPSS version 26. Ethical clearance was obtained from Institutional Review Committee (Reference number: 2025/090).Results: Among 62 participants, the mean age was 7.13 ± 5.48 years with a female predominance (58.06 %). Congenital heart disease (CHD) accounted for 79.03 % of cases, rheumatic heart disease (RHD) for 19.35 %, and cardiomyopathy for 1.61 %. Acyanotic heart disease was present in 90.32 % of cases. Medical management alone was provided to 46.77 %, while 37.09 % were referred and underwent surgery. Overall, 91.93 % showed improved outcomes. Cyanotic status (p